The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jcat.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Aminopropyl-silica-supported Cu nanoparticles: An efficient catalyst for continuous-flow Huisgen azide-alkyne cycloaddition (CuAAC)

Abstract: Cu nanoparticles prepared by metal vapor synthesis (MVS) were immobilized on 3-aminopropyl-functionalized silica at room temperature. HRTEM analysis of the catalyst showed that the copper nanoparticles are present with mean diameters limited in the range 1.0-4.5 nm. TPR analysis was performed in order to study the oxidation state of the supported copper nanoparticles. The supported catalyst was used both in batch and in a packed-bed reactor for continuous-flow CuAAC reaction. The activation of the copper catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…For example, agarose was a cheap and degradable polysaccharide for the stabilization of active CuNP (CuNPs@agarose) in the size range of 4-8 nm in water under low catalyst loading and mild reaction conditions [148]. The 3-aminopropylsilica support was able to stabilize smaller CuNPs with the size in the range of 1-4.5 nm, leading to very high catalytic activity (productivity up to 1689 mol/mol) in continuous-flow click reaction between phenyl acetylene and benzyl azide [149]. A more recent case showed fluorescent aggregates of hexarylbenzene derivatives serving both as reactors and stabilizers for the preparation of 9-17 nm-sized CuNPs with efficient catalysis of CuAAC reactions in excellent yield under solvent-free conditions [150].…”
Section: Cuaacmentioning
confidence: 99%
“…For example, agarose was a cheap and degradable polysaccharide for the stabilization of active CuNP (CuNPs@agarose) in the size range of 4-8 nm in water under low catalyst loading and mild reaction conditions [148]. The 3-aminopropylsilica support was able to stabilize smaller CuNPs with the size in the range of 1-4.5 nm, leading to very high catalytic activity (productivity up to 1689 mol/mol) in continuous-flow click reaction between phenyl acetylene and benzyl azide [149]. A more recent case showed fluorescent aggregates of hexarylbenzene derivatives serving both as reactors and stabilizers for the preparation of 9-17 nm-sized CuNPs with efficient catalysis of CuAAC reactions in excellent yield under solvent-free conditions [150].…”
Section: Cuaacmentioning
confidence: 99%
“…64 The Cu/C system was originally developed by Lipshutz and co-workers as an inexpensive self-stable catalyst, (Figure 15). 93 The analytical data showed that the MVS allowed the deposition of very small copper particles (<5 nm), which were readily oxidized into Cu(I/II) species after being exposed to air. The primary amine groups on the support served not only as a stabilizer of copper nanoparticles, but also as a heterogeneous base enhancing the reactivity in the CuAAC.…”
Section: Alkyne-azide Cycloadditions With Further Heterogeneous Coppementioning
confidence: 98%
“…(Phenyl hydrazine is added to activate the catalyst bed. )93 A copper-containing layered double hydroxide (LDH) was recently employed as heterogeneous catalyst by the Fülöp-group for the synthesis of triazoles in a highpressure/high-temperature continuous-flow reactor (Figure 16). 94 _ENREF_87 The LDH catalyst was readily obtained by controlled co-precipitiation from Cu(NO 3 ) 2 ·3H 2 O and Fe(NO 3 ) 3 ·9H 2 O at alkaline pH 95.…”
mentioning
confidence: 99%
“…I envisioned that if highly active heterogeneous catalysts could be immobilized inside a microchannel, as shown in the previous section, the Huisgen cycloaddition should be competed instantaneously. [129][130][131][132][133][134][135][136] Herein, I describe the development of the first polymeric membranous copper catalyst-installed microflow reactor, and its applicability to the Huisgen cycloaddition of alkenes and organic azides. A variety of triazoles were quantitatively produced within a residence time of a few seconds by using the membranous copper catalyst-installed microflow reactor.…”
Section: )mentioning
confidence: 99%